Analisis Ekonomi Syariah Terhadap Transformasi Digital dalam Keuangan Islam - Sakinah Mawahdah; Yosy Arisandy; Esti Alfiah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to explore how digital technology can be integrated into the Islamic financial system while adhering to the principles of Shariah economics, and to examine the impact of digital transformation on Islamic financial inclusion, the digital divide, and economic justice in countries with large Muslim populations. This research is a library study employing a descriptive qualitative approach. Data were collected by reviewing and analyzing literature relevant to the topic. The data analysis technique used in this study was conducted with ATLAS.ti 25. The findings reveal that: (1) The integration of digital technology holds significant potential to modernize Islamic finance through Shariah-compliant fintech. However, Shariah compliance (prohibition of riba, gharar, and maysir), security, justice, and consumer protection are top priorities. Enhancing digital and Islamic financial literacy is essential for effective and inclusive technology adoption. Collaboration among stakeholders is vital to realize this potential for a just and sustainable economy. (2) Digital transformation offers considerable opportunities to enhance Islamic financial inclusion through efficient and affordable Shariah fintech innovations. The key challenge lies in addressing the digital divide to ensure that the benefits are distributed equitably and do not exacerbate economic injustice.